Creativity and Its Discontents : China's Creative Industries and Intellectual Property Rights Offenses - Pang, Laikwan (Book collections on Project MUSE., 2012)
Laikwan Pang offers a complex critical analysis of creativity, creative industries, and the impact of Western copyright laws on creativity in China.